Search Design Policy, Digital Disruption and Competition Law - Valeria Falce; Massimiliano Granieri (Market and Competition Law Review)
It is debatable whether traditional competition law tools and remedies are able to deal with the digital disruption and whether it is desirable to adjust or even replace categories that have proven to be mainly suited to tackle anticompetitive conducts associated with stable innovations in market where static competition prevails. From a bottom-up perspective, such Grand Question could well be addressed looking at the European Google Shopping case, just adopted at EU level, that will be analysed below with the aim of assessing whether and to which extent the positive antitrust toolbox is flexible enough to effectively cope with the data-driven era.